The effect of tree water uptake on suction distribution in tropical residual soil slope - Mohd Fakhrurrazi, Ishak; Muhammad Farhan, Zolkepli; M. Y. M., Yunus; N., Ali; A., Kassim; M. S. I., Zaini (Elsevier Ltd., 2021)
This study provided an investigation of active root tree zone which is located at the toe of a slope. This section of slope generated matric suction due to tree water uptake. A field monitoring program was carried out to collect matric suction data at slope with two conditions; in absent of a tree and with a tree (Acacia Mangium) located at toe of slope on a tropical residual soil. This soil suction collection is very important to determine the moisture content in soil. When the soil suction is low, it means that the soil is lack of water, which increase the shear strength of the soil compare to soil with more water content. The variation in matric suction values and matric suction profiles response to the tree water uptake and rainfall are investigated. Three soil instruments known as tensiometer and gypsum block (both for suction collection) together with rain gauge (for rainfall collection). Matric suction significantly increased at vicinity of tree at toe of slope compared to slope without tree. The variations of matric suction response due to climate change occur significantly at swallow of the slope and decrease gradually with depth. The decreases of matric suction occur after long duration of intense rainfall. This act as an initial condition before the water uptake driven by active root tree generate to maximum matric suction (low moisture content). Analyses from matric suction profiles revealed that majority of matric suction changes were greater near tree trunk (<4 m) and at shallow depth (0.5 m). The contours of matric suction profiles are presented to reveal moisture flow due to tree water uptake. This investigation provides the viewed contribution of single mature tree significantly alter the matric suction or moisture variation distribution driven by transpiration in an unsaturated soil slope. It takes consideration that preserving mature tree can improved soil properties in modern slope designs.